On the borders of being and knowing : some late scholastic thoughts on supertranscendental being - Doyle, John P., 1930- (Ancient and medieval philosophy., 2012)
Sylvester Mauro, S.J. (1619-1687) noted that human intellects can grasp what is, what is not, what can be, and what cannot be. The first principle, 'it is not possible that the same thing simultaneously be and not be, ' involves them all. The present volume begins with Greeks distinguishing 'being' from 'something' and proceeds to the late Scholastic doctrine of 'supertranscendental being', which embraces both. On the way is Aristotle's distinction between 'being as being' and 'being as true' and his extension of the latter to include impossible objects.